1986
DOI: 10.3109/03630268609046444
|View full text |Cite
|
Sign up to set email alerts
|

Association of the level of Gγchain in the fetal hemoglobin of normal adults with specific haplotypes

Abstract: The levels of G gamma chain in the fetal hemoglobin of more than 40 Black and Caucasian females were determined with a sensitive high performance liquid chromatography procedure and were correlated with their haplotypes, defined by the presence or absence of 10 different restriction sites. Blood was collected during the 16th and 31st week of pregnancy because of a slightly elevated level of Hb F which facilitated the isolation of this protein from a relatively small sample. Four distinct G gamma levels were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…The present study does not support ---------] (A) and/or [-I-1-4-1 (B) on the production of Hb F or °y-globin chain in Japanese and Koreans the idea that the factor regulating the high or low Hb F synthesis may be related to a sub haplotype B and A in our Korean population, although our data are consistent with this in terpretation in our Japanese family sample (table 3). However, more data are needed to test the difference for the % Hb F between in dividuals bearing a subhaplotype B, especially in homozygous form, and those having a sub haplotype A. Hattori et al [8] (table 3). It is very interesting that a subhaplotype B or A is tightly linked to the presence or ab sence of the Xm n I site 5' to the Gy-globin gene, which may be closely related to the high or low Gy-globin gene expression, respectively, among the Japanese and Koreans [Shimizu et al., submitted].…”
Section: [-4-i-] [-4------] [4-f -] and [---------]mentioning
confidence: 99%
See 1 more Smart Citation
“…The present study does not support ---------] (A) and/or [-I-1-4-1 (B) on the production of Hb F or °y-globin chain in Japanese and Koreans the idea that the factor regulating the high or low Hb F synthesis may be related to a sub haplotype B and A in our Korean population, although our data are consistent with this in terpretation in our Japanese family sample (table 3). However, more data are needed to test the difference for the % Hb F between in dividuals bearing a subhaplotype B, especially in homozygous form, and those having a sub haplotype A. Hattori et al [8] (table 3). It is very interesting that a subhaplotype B or A is tightly linked to the presence or ab sence of the Xm n I site 5' to the Gy-globin gene, which may be closely related to the high or low Gy-globin gene expression, respectively, among the Japanese and Koreans [Shimizu et al., submitted].…”
Section: [-4-i-] [-4------] [4-f -] and [---------]mentioning
confidence: 99%
“…The pres ence of the Xm nl site 5' to the c;y-globin gene or the C -» T substitution at -158 base pairs (bp) of its cap site have been thought to be closely related to the elevation of the Gy-globin chain synthesis in some ethnic groups [5][6][7], A close relationship between the pres ence of this Xm nl site and a specific haplotype in the (3-globin gene cluster in some popula tions has also been shown [Shimizu et al, sub mitted]. Hattori et al [8] described the asso ciation of the level of the Gy-globin chain synthesis of normal pregnant women with ele vated fetal hemoglobin (Hb F) with specific haplotypes in the fi-globin gene cluster. How ever, it has been extremely difficult to purify Hb F from the circulating blood of normal adults with less than 1% Hb F [9][10][11], A recent study by Enoki et al [11] has shown that their procedure for the enrichment of Hb F from the adult hemolysate after the modified alkali dénaturation [12] is very useful for the analysis of the Gy/Ay ratio in normal adults.…”
Section: Introductionmentioning
confidence: 99%
“…The Bantu subhaplotype [-F-4----] has also been described to be associated with low Gy levels [21]. On the other hand, homozygosity for a subhaplotype [ -+ + -+ + ] (at the six sites 5' to the 8-globin gene in figure 1) has been re ported to be associated with high Gy levels (60-70%); that for [----------h| with low Gy lev els (25-30%), and that for [H----------] with very low Gy levels (10-15%) in normal pregnant American Black and Caucasian females with slightly elevated Hb F [22], They reported a close correlation between the Xm nl site 5' to the Gy-globin gene and the H in d i site in the (pPpglobin gene. O ur studies in Japanese new borns [17] and Japanese juvenile and adult chronic myelogenous leukemia patients [23] as well as our 15 subjects in the present study have also shown that the polymorphism of the Xm nl site 5' to the Gy-globin gene has a tight correlation with that of the H in d i site in the (ppr globin gene.…”
Section: Discussionmentioning
confidence: 99%
“…[22], the average %Gy value in nor mal adults in Asian and Polynesian population should fall below 40%, which has been thought to be average value [6], because most chromo somes in these ethnic groups have a subhaplo type [+---------] [27,28], It is interesting that the mean ± SD of the %Gy in 60% of Japanese adults examined was reported to be 12.6 ±5.6 (n = 100), that of the remaining 38% was 42.8 ±7.9, and the 2 additional adults had more than 68% Gy [29], Average %Gy value in their study was 26.8%, which is much lower than the average described above [6], This dif ference must be attributed to the ethnical dif ference [29]. In conclusion, there should be close correlations in Japanese adults between a subhaplotype [H----------] and the low Gy value and between a subhaplotype [ -+ + -+ + ] and the high °y value.…”
Section: Discussionmentioning
confidence: 99%
“…A comparable study as described here was conducted over 10 years ago which involved normal pregnant females (both Caucasians and Blacks) with slightly elevated Hb F (0.5–2%) [18]. Quantitation of Hb F was with an alkali denaturation procedure, while the levels of G γ and A γ chains were determined by the same reversed phase HPLC procedure as used in the present study.…”
Section: Discussionmentioning
confidence: 99%